F-Actin Mediated Focusing of Vesicles at the Cell Tip Is Essential for Polarized Growth. Issue 1 (2nd October 2017) - Bibeau, Jeffrey P.; Kingsley, James L.; Furt, Fabienne; Tüzel, Erkan; Vidali, Luis
Abstract : Quantitative analysis and modeling of vesicle diffusion shows that polarized cell growth rates are sustained by actin-based vesicle clustering at the tip. Abstract: F-actin has been shown to be essential for tip growth in an array of plant models, including Physcomitrella patens . One hypothesis is that diffusion can transport secretory vesicles, while actin plays a regulatory role during secretion. Alternatively, it is possible that actin-based transport is necessary to overcome vesicle transport limitations to sustain secretion. Therefore, a quantitative analysis of diffusion, secretion kinetics, and cell geometry is necessary to clarify the role of actin in polarized growth. Using fluorescence recovery after photobleaching analysis, we first show that secretory vesicles move toward and accumulate at the tip in an actin-dependent manner. We then depolymerized F-actin to decouple vesicle diffusion from actin-mediated transport and measured the diffusion coefficient and concentration of vesicles. Using these values, we constructed a theoretical diffusion-based model for growth, demonstrating that with fast-enough vesicle fusion kinetics, diffusion could support normal cell growth rates. We further refined our model to explore how experimentally extrapolated vesicle fusion kinetics and the size of the secretion zone limit diffusion-based growth. This model predicts that diffusion-mediated growth is dependent on the size of the region of exocytosis at the tip and that diffusion-based growth would be significantly slower than normal cell growth. To further explore the size of the secretion zone, we used a cell wall degradation enzyme cocktail and determined that the secretion zone is smaller than 6 μm in diameter at the tip. Taken together, our results highlight the requirement for active transport in polarized growth and provide important insight into vesicle secretion during tip growth.